2015
DOI: 10.1177/0363546515608162
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Capsular Repair for Symptomatic Hip Instability After Previous Hip Arthroscopic Surgery

Abstract: Revision hip arthroscopic surgery for capsular repair in patients with symptomatic instability after hip arthroscopic surgery provides good functional outcomes at a minimum of 1 and 2 years postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 27 publications
1
87
1
2
Order By: Relevance
“…10 Several surgical techniques showed that viewing from outside the capsule could be helpful in performing secure capsular closures. 1,11 In agreement with these reports, we believe scope viewing from outside the capsule can provide better visualization. The indications of a shoelace complete capsular closure technique are BDDH, FAI, and capsular laxity if indicated and DDH undergoing shelf acetabuloplasty as shown in Table 1.…”
Section: Discussionsupporting
confidence: 87%
“…10 Several surgical techniques showed that viewing from outside the capsule could be helpful in performing secure capsular closures. 1,11 In agreement with these reports, we believe scope viewing from outside the capsule can provide better visualization. The indications of a shoelace complete capsular closure technique are BDDH, FAI, and capsular laxity if indicated and DDH undergoing shelf acetabuloplasty as shown in Table 1.…”
Section: Discussionsupporting
confidence: 87%
“…25,33 Interportal and T-shaped capsulotomy is now accepted as a standard step in central compartment access because it allows a better exposure of the posterolateral/inferior aspects of the joint and nonconstrained manipulation of the instruments. [34][35][36][37] Some published reports about cases of acute hip dislocation after large unrepaired capsulotomy [38][39][40][41] raised concerns about iatrogenic hip instability after arthroscopy, and some authors now recommend meticulous capsule closure in all cases. [41][42][43][44] The next step in hip arthroscopy is to repair the labrum and cartilage lesions.…”
Section: Surgical Techniquementioning
confidence: 99%
“…[10][11][12][13][14] As hip arthroscopy is increasingly used for the treatment of femoroacetabular impingement, we have identified and treated several patients with postoperative instability after hip arthroscopic surgery. 15 As such, we believe that a watertight capsular closure after routine hip arthroscopy is important for preventing postoperative instability and improving patient outcomes. We detail our technique for primary capsular closure of an intraportal capsulotomy using figure of eight sutures to obtain a watertight capsular seal.…”
mentioning
confidence: 98%